2017
DOI: 10.15226/2381-2907/3/5/00144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Identification of Bovine Ixodide Tick in Dandi District, West Shoa Zone, Oromia Region, Ethiopia

Abstract: A cross-sectional study was conducted with the aim of identifying and estimating the prevalence of cattle ixodid tick infestation with respect to host related factors in Dendi district, Western Shoa, Ethiopia. Adult ixodid ticks were collected from 384 randomly selected cattle by using forceps and preserved in separate collecting bottle with 70 % ethyl alcohol. The collected ticks were identification under stereomicroscope into generas and species based on their morphology. The present study revealed that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…Moreover, females undergo high lactation, pregnancy, and production stress which makes them more prone to infections [28]. In corroboration to our findings, a higher tick infestation in female animals has been reported by other workers also [29,30,31]. In the present study, crossbred cattle were found infested more with the ticks as compared to the indigenous cattle.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, females undergo high lactation, pregnancy, and production stress which makes them more prone to infections [28]. In corroboration to our findings, a higher tick infestation in female animals has been reported by other workers also [29,30,31]. In the present study, crossbred cattle were found infested more with the ticks as compared to the indigenous cattle.…”
Section: Resultssupporting
confidence: 92%
“…This variation may be related to the fact that female animals are kept properly in the house with a good management system for dairy purposes, whereas male animals graze the field all day, leaving them vulnerable to tick infestation. This finding contradicts the findings of ( Amante, 2020 ) in Jardega Jarte, as well as ( Haile, 2017 ) in the Dandi district.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding is consistent with previous work in Diga town reported by ( Tadesse et al, 2012 ) (12.3%) and ( Tafesse and Amante, 2019 ) (16%). However, ( Haile, 2017 ) reported the lowest prevalence (3.6%) in Dandi districts. According to Pegram et al, 1981, this species has no preference for a specific altitude, rainfall zone, or season; it is also known to transmit tick paralysis in Harar, Ethiopia.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The current study's mean TVC did not meet the 5log cfu/mL requirement for raw milk intended for direct human consumption [ 28 ] Similarly, higher mean TVC values (6.36–9.82 log cfu/mL) were discovered in various Ethiopian regions [ 7 , 30 ]. The increased count in milk could be attributed to poor hygiene practices used during manufacturing and subsequent handling [ 31 ].…”
Section: Discussionmentioning
confidence: 92%